2006
DOI: 10.1111/j.1467-842x.2006.tb00456.x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of rotavirus‐related illness among young children on the Australian health care system

Abstract: R otavirus (RV) is a major cause of acute gastroenteritis (AGE) in children under the age of fi ve and is a signifi cant cause of early childhood mortality in developing countries and morbidity in developed countries.1 Estimates for Australia from the mid 1990s put the direct national healthcare burden of RV at 10,000 hospital admissions 2 and 50,000 primary care visits 3 annually. These estimates were compiled to provide primary data for a cost-effectiveness analysis of RV vaccination in Australia. 3The previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 13 publications
4
56
0
Order By: Relevance
“…17 For every child living in a high-income country who is admitted to hospital with rotavirus gastroenteritis, between five and ten are seen in primary care or outpatient clinics, and 32 children are managed at home. 10,18,19 A recent European study reported that 41% of 2,712 children under 5 years of age seeking care for gastroenteritis symptoms had rotavirus detected. 19 In this study, 50% of gastroenteritis cases presenting to Emergency Departments or admitted to hospital and 27% managed in primary care were caused by rotaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…17 For every child living in a high-income country who is admitted to hospital with rotavirus gastroenteritis, between five and ten are seen in primary care or outpatient clinics, and 32 children are managed at home. 10,18,19 A recent European study reported that 41% of 2,712 children under 5 years of age seeking care for gastroenteritis symptoms had rotavirus detected. 19 In this study, 50% of gastroenteritis cases presenting to Emergency Departments or admitted to hospital and 27% managed in primary care were caused by rotaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrheal disorders in childhood account for a large proportion (18%) of childhood deaths, making it the second most common cause of child deaths worldwide. Additional risks include young age, immunodeficiency, measles, malnutrition, and lack of exclusive or predominant breast-feeding 1,7,8 . The broad principles of management of acute gastroenteritis in children include oral rehydration therapy, enteral feeding and diet selection, zinc supplementation, and additional therapies such as probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics are required, however, for bacterial gastroenteritis complicated by septicaemia and in cholera, shigellosis, amoebiasis, giardiasis, and enteric fever 14 . In developing countries, oral zinc given at the onset of symptoms decreases the duration and severity of acute diarrhea and is recommended by the WHO 8,15 . The NICE guidelines published in april 2009 guidelines looked at therapeutic options such as probiotics and antiemetics but were unable to find evidence to recommend them 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Although deaths are rare in high-income countries such as Australia, the incidence of infection is similar to lower income countries, with almost all children having at least one rotavirus infection before their 5th birthday (83). Prior to rotavirus vaccine introduction, rotaviruses caused considerable morbidity in Australia, resulting in an estimated 10,000 hospitalisations, 22,000 ED presentations, and over 110,000 general practitioner (GP) consultations annually among children in this age group (84). Moreover, Indigenous people are disproportionately affected by severe rotavirus infection, with Indigenous Australian infants five times more likely to be hospitalised for rotavirus, and if hospitalised, to have a longer length of stay than non-Indigenous infants (85,86).…”
Section: Rotavirusmentioning
confidence: 99%
“…A review of 17 post-licensure studies assessing the VE of a single dose of Varivax in the United States in 2008 found that one dose of VV was 84.5% (median; range, 44% to 100%) effective in preventing all varicella and 100% effective (mean and median) in preventing severe varicella (69). A meta-analysis of 27 studies published between 1995 and 2014 reporting VE of one dose of either of the licensed varicella vaccines, found the pooled one dose VE against all varicella and moderate-severe varicella was 81% (95% CI: [78][79][80][81][82][83][84] and 98% (95% CI: 97-99), respectively (70).…”
Section: Previous Acellular Pertussis Vaccine Effectiveness Estimatesmentioning
confidence: 99%